The impact of medieval Armenian national-liberation eschatology on the psychology of the masses and military-political projects of the 16th and 18th centuries - A.M. Ayvazyan (Ученые записки Казанского университета: Серия Гуманитарные науки)
In the 10th – 18th centuries, a number of popular prophecies, visions, and legends in Armenian written sources were united by the theme of the liberation of Armenia from Muslim rule with the military help of the great Christian powers. In Armenian historiography, these narratives received the cumulative name of the “liberation legend”. After the destruction of the last Armenian kingdom in Cilicia (1375) and the final decline of the major Armenian principalities in the territory of Armenia (during the late 15th century), the liberation legend's impact on the psychology of the masses increased. The process of frustration in their own forces was directly proportional to the uncritically growing faith in the Christian powers' imminent military intervention for the liberation of Armenia. It seems that the national belief in the tenets of the legend was a kind of adaptive mechanism for the ethno-psychological self-defense and survival of the Armenian people. The military-political projects for the liberation of Armenia drafted in the 16th – 18th centuries, were invariably taking into account both rational (military-strategic) and irrational (ethno-psychological) factors, including the widespread expectations from the liberation legend's narrative motifs. In the 1720s, however, the legend completely failed to hold out against the historical reality and disappeared forever from the political agenda of the Armenian leadership.